Brands, consumers, symbols, & research Sidney J. Levy on marketing - Levy, Sidney J., 1921-; Rook, Dennis W.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
This volume assembles all Sidney J. Levy's and his collaborators' significant essays and studies in the field of marketing. His work includes marketing's role in management, how managers develop products and brands and how the marketplace is studied.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Marketing -- United States; Advertising -- United States; Consumer behavior -- United States; Electronic books